Роль нейронних мереж у розробці систем керування для автономних транспортних засобів - Чайка, В. Є. (ХНУРЕ, 2025)
This work explores the significant role of neural networks in the development of control systems for autonomous vehicles (AVs). It discusses how neural networks are utilized in various aspects of AVs, including perception, decision-making, and motion control, enabling vehicles to operate safely and efficiently in complex environments. The paper highlights recent advancements and real-world applications of neural network-driven systems. Additionally, the article addresses the challenges remaining in the field, such as handling edge cases and improving system robustness. It also explores potential future improvements, including advancements in explainable AI and hybrid models, that could enhance the reliability and efficiency of AV control systems.
Keywords: автономна система керування; автономний транспортний засіб